E?ciency of Analgesic E?ects of Nsaids and Opioids in Ureteric Colic Patients - MR Keshava Murthy; Aruna C Ramesh; K N Vikas (Academia Anesthesiologica International, 2021)
Background: Evidences indicate that renal colic is the very painful conditions that will require very urgent pain relief. Patients who are suffering from renal colic usually do not recover from pain using pain killers. Hence, considerable percentage of patients will be admitted to the emergency department usually be used as pain relievers in the emergency department are non-steroidal antiinflammatory drugs and/or intravenous opioids for effective pain relief. Subjects and Methods: A retro respective study, comparing intravenous single-dose paracetamol and combination    of paracetamol, Hyoscine, diclofenac suppository and fentanyl for ureteric colic patients presenting in the emergency medicine department. Results: Ureteric colic seen in predominantly with 18-40 age group with Male Predominance. Majority of patients presented with pain abdomen with NRS of 0-6. Paracetamol and Hyoscine Used in 44% of cases, Diclofenac in Combination in 34% and along with fentanyl in 22%. Duration of Stay less than 24 hours in combination of paracetamol , Hyoscine and Diclofenac suppository combination when fentanyl used patients length of stay 24hours in 12%. Patients with NRS 0-6 majority of patients required paracetamol, Hyoscine and diclofenac suppository and Patient with NRS >7 (20%) Patients required fentanyl. Conclusion: In our study concluded that patient with mild to moderate pain paracetamol and diclofenac suppository shown good results and with severe pain additional analgesics fentanyl is used.